2012
DOI: 10.1136/jnnp-2012-303013
|View full text |Cite
|
Sign up to set email alerts
|

Tremor in inflammatory neuropathies

Abstract: Tremor in inflammatory neuropathies is common, adds to disability and yet does not often respond to treatment of the underlying neuropathy. When present, tremor severity is associated with F wave latency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 30 publications
11
76
0
3
Order By: Relevance
“…5 This indicates a second mechanism may be necessary to produce tremor. Here we set out to explore aspects of CNS physiology in tremulous and nontremulous patients with inflammatory neuropathies compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 This indicates a second mechanism may be necessary to produce tremor. Here we set out to explore aspects of CNS physiology in tremulous and nontremulous patients with inflammatory neuropathies compared to healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 However, we have shown that although conduction velocity does not predict the presence of tremor, it is correlated with its severity for those in whom tremor is present. 5 This indicates a second mechanism may be necessary to produce tremor. Here we set out to explore aspects of CNS physiology in tremulous and nontremulous patients with inflammatory neuropathies compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In inflammatory neuropathies tremor is found in up to 80 % of cases with IgM paraproteinemic neuropathy [129,130]. Clinically, neuropathic tremor mostly presents as postural or kinetic tremor [131].…”
Section: Tremor In Peripheral Neuropathiesmentioning
confidence: 99%
“…Others reported improvement after pregabalin (30-80 mg) [132,133]. However, in a recent series no patient responded to medication prescribed for tremor, but some reported improvement after treatment for their neuropathy (intravenous immunoglobulin, rituximab or chemotherapy regimen consisting of cyclophosphamide, hydroxydaunorubicin, oncovin and prednisone plus rituximab (CHOP-R) chemotherapy) [129]. DBS of the thalamus (Vim) has been described successful in cases of hereditary neuropathy [134][135][136].…”
Section: Tremor In Peripheral Neuropathiesmentioning
confidence: 99%